2016
DOI: 10.4102/sajr.v20i2.1048
|View full text |Cite
|
Sign up to set email alerts
|

Imaging for cardiac electrophysiology

Abstract: Clinical cardiac electrophysiology is the study of the origin and treatment of arrhythmia. There has been considerable recent development in this field, where imaging has had a transformational impact. In this invited review, we offer a global overview of the most important developments in the use of imaging in cardiac electrophysiology. We first describe the radiological imaging modalities involved in cardiac electrophysiology, to assess cardiac anatomy, function and scar. We then introduce an imaging modalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The CDA form was proposed as an optimal and consistent structure for transferring information in comprehensive health information exchange infrastructure of Iran. [ 15 ] Accordingly, all SNOMED-CT reference codes and terms were structured in the form of CDA body and title. Finally, the Extensive MarkUp Language (XML) rules were defined, and the final communication protocol was prepared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDA form was proposed as an optimal and consistent structure for transferring information in comprehensive health information exchange infrastructure of Iran. [ 15 ] Accordingly, all SNOMED-CT reference codes and terms were structured in the form of CDA body and title. Finally, the Extensive MarkUp Language (XML) rules were defined, and the final communication protocol was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure has a remarkably high success rate and can enhance the patient's quality of life to a large extent. [ 13 14 15 16 17 ] Thus, it is necessary to standardize reporting and create exchange protocol of EPS ablation information. To tackle this issue, the present study proposes a communication protocol to drive interoperability among ISs involved in EPS ablation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Some of arrhythmias including postinfarct arrhythmia are instantly fatal if other arrhythmias are not instantly fatal but lead to important complications such as strokes. [ 3 ] Substantial advances in the treatment of arrhythmias as well as technological enhancements have allowed EP studies (EPSs) to be considered as an important subspecialty in cardiology. Currently, catheter ablation is the first or second line of treatment for the various cardiac arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…Current image integration techniques (eg, CARTO-Merge, Biosense Webster, Diamond Bar, CA, USA) incorporate computed tomography (CT) imaging or magnetic resonance imaging (MRI) into the 3D mapping system and are widely used in clinical practice [Kistler 2006;Desjardins 2016]. Although most previous studies have concluded that image integration has a positive influence on clinical outcomes [Marai 2016;Shigenaga 2016] and although other important parameters have been identified [Bertaglia 2009], the most commonly used index for evaluating the accuracy of ablation is comparison of the actual distances (between the ablation and image planes, guided by image integration) with the predicted distances (between the fluoroscopy and image planes, not guided by image integration) [Kimura 2013].…”
Section: Introductionmentioning
confidence: 99%